Plantlet Regeneration from Seedling Explants of Sweet Gourd (Progressive Agriculture, 2014)
To regenerate plantlets both directly and indirectly, different explants (cotyledon, hypocotyl, root tip and shoot tip) of sweet gourd (Cucurbita moschata) were cultured on medium supplemented with different concentrations and combinations of NAA (0.0, 0.2, 0.5 and 1.0 mg/L) and BAP (0.0, 0.5, 2.0 and 5.0 mg/L). Cotyledon explants performed best in callus induction. The combination of 5 mg/L BAP and 0.2 mg/L NAA produced the highest callus frequency in cotyledon (90.0%). The calli derived from cotyledon, hypocotyl and root tip were cultured in MS medium supplemented with different concentrations of kinetin, BAP and/or NAA for shoot induction. Regeneration via callus was achieved only from cotyledon calli at a frequency of 65.0% on 2 mg/L BAP and 0.2 mg/L NAA. Shoot tips cultured for direct regeneration, in the same media containing 1 mg/L BAP or 1 mg/L BAP + 0.2 mg/L NAA resulted in 100.0% shoot differentiation. The regenerated shoots rooted on MS medium with or without 0.1 mg/L NAA (100%).DOI: http://dx.doi.org/10.3329/pa.v18i2.18093 Progress. Agric. 18(2): 61 - 66, 2007